2017
DOI: 10.1111/aogs.13098
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of maternal, fetal and neonatal outcomes in the setting of cesarean section in low‐ and middle‐income countries

Abstract: Introduction Cesarean section (CS) rates are increasing globally with an unclear effect on pregnancy outcomes. The study objective was to quantify maternal and perinatal morbidity and mortality in low- and middle-income countries associated with CS compared to vaginal delivery (VD) both within and across sites. Material and methods A prospective population-based study including home and facility births in 337,153 women with a VD and 47,308 women with a CS from 2010 to 2015 was performed in Guatemala, India, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 17 publications
7
65
1
Order By: Relevance
“…This suggested that the coverage of maternal health services utilization has been improved after years of development, which is consistent with the result of a study comparing the inequality status of maternal health services utilization before and after health care reform in Shaanxi Province[11]. The rates of C-section in our study exceeded the WHO recommended level and were also higher than those from other studies in Bangladesh and African sites [22, 23]. The high prevalence of C-section showed that some surgeries were likely to be clinically unnecessary.…”
Section: Discussionsupporting
confidence: 91%
“…This suggested that the coverage of maternal health services utilization has been improved after years of development, which is consistent with the result of a study comparing the inequality status of maternal health services utilization before and after health care reform in Shaanxi Province[11]. The rates of C-section in our study exceeded the WHO recommended level and were also higher than those from other studies in Bangladesh and African sites [22, 23]. The high prevalence of C-section showed that some surgeries were likely to be clinically unnecessary.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings from Uganda were consistent with those from high‐income countries, indicating that vacuum extraction is a safe intervention and that SSCD carries an increased risk of maternal adverse events . Indeed, one study found maternal and neonatal mortality to be higher following cesarean delivery compared with vaginal, especially in African countries …”
Section: Discussionsupporting
confidence: 88%
“…A potential limitation of the present study was the observational design; however, a randomized trial would have been unethical owing to the exposure of many more participants to the increased risks of surgery and a lengthened waiting time, with increased risk of birth asphyxia and adverse maternal outcomes . Consequently, the current results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 88%
“…In some African countries, cesarean deliveries are associated with a very high maternal and neonatal mortality and morbidity. This is due to the absence of facilities for instrumental vaginal delivery, delayed performance of CSs, and inadequate facilities/skills . In these countries the situation is even more complicated, since rural areas exhibit insufficiently low CS rates while urban areas exhibit exceedingly high CS rates.…”
mentioning
confidence: 99%
“…This is due to the absence of facilities for instrumental vaginal delivery, delayed performance of CSs, and inadequate facilities/skills. 9 In these countries the situation is even more complicated, since rural areas exhibit insufficiently low CS rates while urban areas exhibit exceedingly high CS rates. The worldwide increase in cesarean deliveries needs to be "Too many CSs, too many episiotomies."…”
mentioning
confidence: 99%